La dimensión social del Pirineo. Desarrollo endógeno y cooperación - Silván Sada, Luis (Geographicalia, 2017)
The Pyrenees as a range of mountains and humanised space arouse the interest of their inhabitants and other people that keep up more or less relations with them even though its social dimension is identified with the first. Over its social space underlies the feeling of belonging to the same way of life and culture, to an only Pyrenees. However the structure of its population is weakened, variable from the point of view spatial, and sensitive to external crisis. From that it follows the necessity and the urgency of applying there a self-development based in their own and enough social-space resources (for example, the Valley of Tena). For that is absolutely essential the personal contribution of the local populationand an effort towards cooperation in every level and in every direction.
Keywords: Mountain; Pyrenees; social space; self-development; transfrontier cooperation.